Caffeine supplementation does not increase performance on professional soccer official matches - Ronaldo Angelo Dias da Silva; Rafael de Oliveira Idelfonso; Bruno Pena Couto; Marcos Daniel Motta Drummond (Revista Brasileira de Ciências do Esporte)
ABSTRACT To investigate the acute effect of caffeine on performance in official soccer matches, a double-blind, balanced crossover design was applied to 13 professional male Brazilian soccer players in the first division of the state championship. Supplementation was carried out of caffeine (400mg, approximately 6mg/kg) in capsule form or a placebo. No effect of supplementation on the total distance covered (p=0.53; CI95%=-370, 796; d=0.22) or the total distance covered at different speeds (all p≥0.45; CI95%=-40.14, 84.57; ŋp2=0.048), acceleration (p=0.38; CI95%=-5.67, 11.8; ŋp2=0.06; d=0.22), number of sprints (p=0.52; CI95%=-1.55, 2.63; d=0.16), HRmean (p=0.52; CI95%=-1.87, 3.49; ŋp2=0.03; d=0.22), HRmax (p=0.10; CI95%=-6.69, 0.77; ŋp2=0.19; d=0.00), RPE (p=0.15; CI95%=-0.258, 1.48; d=0.50) or efficacy index (p=0.48; CI95%=-0.06, 0.12; ŋp2=0.04; d=0.22). Therefore, acute caffeine supplementation not effective to increase the performance of soccer players in official matches.